2011
DOI: 10.1090/s0894-0347-2011-00707-8
|View full text |Cite
|
Sign up to set email alerts
|

A proof of the positive density conjecture for integer Apollonian circle packings

Abstract: An Apollonian circle packing (ACP) is an ancient Greek construction which is made by repeatedly inscribing circles into the triangular interstices in a Descartes configuration of four mutually tangent circles. Remarkably, if the original four circles have integer curvature, all of the circles in the packing will have integer curvature as well. In this paper, we compute a lower bound for the number κ ( P , X ) \kappa (P,X) of integers less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 14 publications
0
60
0
Order By: Relevance
“…Other results in this rapidly developing area include the extensive development regarding Apollonian packings [S07,S09,KO11,BF11] and orbits of thin subgroups more generally [K09,BK10,KO12]. We refer to [K, O11, O14] for recent comprehensive surveys on this subject.…”
Section: Alexander Gorodnik and Amos Nevomentioning
confidence: 99%
“…Other results in this rapidly developing area include the extensive development regarding Apollonian packings [S07,S09,KO11,BF11] and orbits of thin subgroups more generally [K09,BK10,KO12]. We refer to [K, O11, O14] for recent comprehensive surveys on this subject.…”
Section: Alexander Gorodnik and Amos Nevomentioning
confidence: 99%
“…For example, if P is taken to be the packing generated by (−1, 2, 2, 3), it is shown that P 24 = {2, 3, 6, 11, 14, 15, 18, 23} and that all integers 10 6 < x < 5 · 10 8 such that x ∈ P 24 modulo 24 appear as curvatures in P . An immediate consequence of Conjecture 4.1 is the positive density conjecture of Graham et al in [27] that the curvatures in a given packing have positive density in N which was first proven in [8]. In this section we outline the proof of this positive density conjecture and survey what is currently known about this density and about the local-to-global conjecture above.…”
Section: Conjecture 41 (Fuchs and Sandenmentioning
confidence: 87%
“…Indeed, this remarkable integrality feature gives rise to several natural questions about integer ACPs; Graham et al make some progress towards answering them in [27] and pose striking conjectures, many of which are now theorems or at least better understood (see [7], [8], [9], [13], [19], [20], [21], [22], [32], [46], etc.) In this article we will survey how all these questions are handled and give an overview of what is currently known.…”
Section: Theorem 12 (Descartes 1643) Let a B C And D Denote Thementioning
confidence: 99%
See 2 more Smart Citations